COVID-19 catalyst: emergent pedagogies and a DIAgram framework. (5th July 2022) - Tregloan, Kate; Samayoa, Nancy; Chu, Adrian; Jativa, Fernando
Abstract : The global COVID-19 pandemic has delivered extraordinary challenges across geographies as well as practices, and clearly academia has not been spared. While the events of 2020 and 2021 have revealed some limits to teaching in the 'old (pre-pandemic) normal', technology-supported pedagogies have been emerging for several years. This pandemic has been a potent catalyst, not only for ad-hoc adaptation, but potentially for long-term change and improvement. The 'old normal' is now long passed, and approaches to learning and teaching continue to explore new ground. This article draws on the work of Built Environments Learning + Teaching (BEL+T), an academic group within the Faculty of Architecture, Building and Planning at the University of Melbourne. The BEL+T group applies creative problem-solving and design-led approaches, evidence-based research methodologies and project-focused consultancy to improve teaching quality and student engagement in built environment disciplines. The following sections introduce a learning design framework – the Delivery, Interaction, Assessment (DIA) framework – which was developed by BEL+T as a tool to communicate with and support staff throughout 2020 and 2021, and continues to be used to support teaching efforts. The translation of the elements of the DIA framework and its related 'DIAgram' to specific learning activities are presented in the following sections 'on the (virtual) ground'. Some emergent pedagogies for virtual learning environments (VLEs) are outlined, exploring relationships between students, teachers, objects, sites and VLEs for learning, alongside implications for teacher presence and performance online. These key factors have influenced online approaches both before and since the onset of the pandemic. They deliver implications for emergent hybrid approaches such as dual delivery and blended synchronous learning, which are in turn driven by the needs of a still-distributed student cohort and the challenges of ongoing unpredictability.